Intellektual kamchiligi bo‘lgan bolalar mehnat ta’limi va madaniy gigiyenik ko‘nikmalarni shakllantirish - Bozorboyev Javlon, Berdiyorov Xurshid (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this article, labor education of children with intellectual disabilities and the formation of cultural hygiene skills are scientifically analyzed. Also, in the article, the current educational system in our republic serves to develop children's mental abilities through independent thinking, and by forming their labor education and labor hygiene skills, they can be used in society in the future. opinions about finding places are highlighted.